Quality of life of the elderly in urban and rural areas in Serbia - Urošević Jadranka; Odović Gordana; Rapaić Dragan; Davidović Mladen; Trgovčević Sanja; Milovanović Verica (Vojnosanitetski Pregled)
Background/Aim. The number of elderly people in the world is growing, in Serbia as well. Serbia is already among the top ten countries with the oldest population, it is the fact. Aging influences the quality of life in different ways. The aim of this study was to assess the health-related quality of life of the elderly in urban and rural areas in Serbia. Methods. The study included 100 elderly people aged 65 years and above in urban and rural areas in Serbia. The next questionnaires were used: a sociodemographic questionnaire and a Serbian version of standardized European Euro-QoL questionnaire (EQ-5D-3L), as a basic index for the assessment and description of the quality of life. Results. In the structure of the respondents, according to the achieved social contacts (p = 0.012), the life of those with family members (p = 0.009), and health status (p = 0.000), in relation to the place of residence there was a statistically significant difference. There was a significant difference (p = 0.040), predominantly poor score for anxiety/depression within the rural population. The average value of quality of life in urban and rural areas was not statistically significant (p = 0.720). For those living in rural areas there was a statistically significant positive correlation between anxiety/depression and age, wealth status, marital status, living with family members and achieving social contacts, while a negative correlation was observed between anxiety/depression and education. Conclusion. On the basis of the data of our study, we can say that the presence of anxiety/depression among older people is greater in rural than in urban areas. The results of this study show that the perception of anxiety/depression among older in rural areas is bigger with the age and poverty increasing, the loss of a spouse, life without family members, lack of achievement of social contacts and lower education.